THE EXISTING APPROACHES AND METHODS OF FORECASTING OF DEMAND FOR CONTAINER TRANSPORTATIONS - A. Perminova (Вестник университета)
The methodical principles of the analysis of the object of forecasting are considered. The main approaches to forecasting (historical, system and complex ) are analysed. Three main groups of methods of forecasting are allocated: expert (intuitive), formalized and combined.